THE INFLUENCE OF LEADERSHIP STYLE, WORK MOTIVATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF EDUCATORS AT SMKN 2 BANDAR LAMPUNG - Mei Novitasari Sitorus; Iskandar Ali Alam (ZILLZELL MEDIA PRIMA, 2024)
The study aims to measure the impact of leadership style, work motivation, and working environment conditions on teaching efficiency at SMKN 2 Bandar Lampung. A quantitative approach was chosen as the research method, with data collected directly from teachers through questionnaires, covering a total population of 31 educators. The collected data was then analyzed using multiple linear regression models. The results of the analysis showed that leadership style did not have a meaningful impact on efficiency in the teaching process. Meanwhile, work motivation factors were found to have a significant influence. Related to the work environment, the results of the analysis showed no significant influence. It is hoped that the findings from this study can contribute to improving the quality of teaching at SMKN 2 Bandar Lampung, by paying special attention to work motivation variables, while leadership styles and working environment conditions may require further evaluation in different contexts.